Anti-Inflammatory Drug Candidates for Prevention and Treatment of Cardiovascular Diseases - Quentin Delbaere; Nicolas Chapet; Fabien Huet; Clément Delmas; Nathan Mewton; Fabrice Prunier; Denis Angoulvant; François Roubille (MDPI AG, 2023)
Incidence and mortality rates for cardiovascular disease are declining, but it still remains a major cause of morbidity and mortality. Drug treatments to slow the progression of atherosclerosis focus on reducing cholesterol levels. The paradigm shift to consider atherosclerosis an inflammatory disease by itself has led to the development of new treatments. In this article, we discuss the pathophysiology of inflammation and focus attention on therapeutics targeting different inflammatory pathways of atherosclerosis and myocardial infarction. In atherosclerosis, colchicine is included in new recommendations, and eight randomized clinical trials are testing new drugs in different inflammatory pathways. After a myocardial infarction, no drug has shown a significant benefit, but we present four randomized clinical trials with new treatments targeting inflammation.